Neuroprotective efficacy of aminopropyl carbazoles in a mouse model of amyotrophic lateral sclerosis - Tesla, Rachel (National Academy of Sciences, 2012)
We previously reported the discovery of P7C3, an aminopropyl carbazole having proneurogenic and neuroprotective properties in newborn neural precursor cells of the hippocampal dentate gyrus. We have further found that chemicals having efficacy in this in vivo screening assay also protect dopaminergic neurons of the substantia nigra following exposure to the neurotoxin 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine, a mouse model of Parkinson disease. Here, we provide evidence that an active analog of P7C3, known as P7C3A20, protects ventral horn spinal cord motor neurons from cell death in the G93A-SOD1 mutant mouse model of amyotrophic lateral sclerosis (ALS). P7C3A20 is efficacious in this model when administered at disease onset, and protection from cell death correlates with preservation of motor function in assays of walking gait and in the accelerating rotarod test. The prototypical member of this series, P7C3, delays disease progression in G93A-SOD1 mice when administration is initiated substantially earlier than the expected time of symptom onset. Dimebon, an antihistaminergic drug with significantly weaker proneurogenic and neuroprotective efficacy than P7C3, confers no protection in this ALS model. We propose that the chemical scaffold represented by P7C3 and P7C3A20 may provide a basis for the discovery and optimization of pharmacologic agents for the treatment of ALS.